Frequency of food consumption in teens and young adults with Down syndrome - October 2017 - Barco Díaz, Mayra Guisela (2019)
Objective: To describe the frequency of food consumption in teens and young adults with Down syndrome from three private workshops. Materials and methods: A questionnaire on the frequency of food consumption was administered to the study population’s parents to find out their children’s food habits. Results: Fifty-five percent (55 %) of the study population consumed dairy products on a daily basis, 60 % lean meat 3 to 4 times per week, 75 % legumes 3 to 4 times per week, 5 % fish 4 times or more per week, 15 % eggs 3 times per week, 45 % fruits daily, 25 % greens and vegetables every day, 100 % sweetened beverages daily, 45 % cakes or cookies during the week, 40 % butter or margarine during the week, 30 % sausages and lunch meats during the week, and 40 % candies during the week. Conclusions: More than half of the participants had an adequate consumption of dairy products, lean meat and legumes, but an inadequate consumption of fish, eggs, and greens and vegetables. Furthermore, the consumption of sweetened beverages, cakes or cookies, butter or margarine, sausages and lunch meats, and candies was inadequate. Fruit variety and mode of consumption were also inadequate.